Pengaruh Total Assets Turnover dan Current Ratio terhadap Return on Assets pada Perusahaan Properti dan Real Estate di BEI (2014-2018) - Hanna Arsyanti; Fifi Afiyanti Tripuspitorini; Djoni Djatnika (Indonesian Journal of Economics and Management, 2020)
The research in this final project was toi know and analyze The Effect of Total Assets Turnover and Current Ratio to Return On Assets in Property and Real Estate Companiesl on the Indonesian Stock Exchange in the periode 2014-2018. The type of data used is secondary data in the form of the company’s annuall financial statement. In the research, there are 7 Property and Reall Estate Companies on the Indonesia Stock Exchangei which are sampled research. The research method used is descriptive and quantitative research. The test is done by panel data regression which eviews 10. The selected panell data regression method is Fixed Effect Model. The research result show that Total Assets Turnover has a positive impactt to Return On Assets and Current Ratio has not impact to Return On Assets. Total Assets Turnover and Current Ratio have a simultaneous effect to Return On Assets.